Логічні парадокси та їх роль у пізнанні - Більчук, О. С. (ХНУРЕ, 2022)
Logic is an abstract science based on the analysis of real thinking. The inconsistency of logical theory and practice of thinking mostly arises in the form of paradox, and sometimes in the form of logical antinomy. Theses tell about the paradoxes of logic, which are an element of the process of cognition. The division into syntactic and semantic paradoxes, its vagueness and inaccuracy is analyzed.
Keywords: логічні парадокси; пізнання